1951
DOI: 10.1111/j.1748-1716.1951.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Administration of Atropine and Pilocarpine on the Submaxillary Gland of the Cat.

Abstract: Some days after parasympathetic decentralisation of the submaxillary gland, brought about by cutting the chorda tympani, the secretory cells of the gland show an increased sensitivity t o chemical agents. This was first demonstrated by MAEVSKY (1923), using adrenaline as a secretory stimulus. The "paralytic secretion'' of saliva appearing after cutting the chorda (CLAUDE BERNARD, 1864) is very likely evoked by adrenaline (noradrenaline) acting on the supersensitive gland cells, since it is observed only under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1963
1963
2001
2001

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…2 shows that the results are similar to those obtained after section of the chorda-lingual nerve, indicating that if there was such damage to postganglionic neurons it was negligible. contralateral gland [Emmelin, Jacobsohn and Muren, 1951]. In the present studies a similar gain of weight, though not necessarily significant, was also observed.…”
Section: Denervated Glandssupporting
confidence: 72%
“…2 shows that the results are similar to those obtained after section of the chorda-lingual nerve, indicating that if there was such damage to postganglionic neurons it was negligible. contralateral gland [Emmelin, Jacobsohn and Muren, 1951]. In the present studies a similar gain of weight, though not necessarily significant, was also observed.…”
Section: Denervated Glandssupporting
confidence: 72%
“…The ultrastructural appearance of the chorda included in the ligation is one of extensive loss of axons and demonstrates the damage that the parasympathetic supply suffers by inclusion of the chorda. Destruction of the chorda is itself followed by glandular atrophy (10)(11)(12)(13), which was reported to be greater in rodents (14).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both procedures induce a supersensitivity of the cat's submaxillary gland to secretory agents [Emmelin, Jacobsohn and Muren, 1951]. When given repeatedly to rats for 1 week the doses of atropine used in the present investigation were found to increase the sensitivity of the submaxillary gland to secretory agents, such as adrenaline and isoprenaline.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, a supersensitivity to secretory agents develops in chronically denervated glands according to Cannon's 'Law of Denervation'. The effect of atropine treatment (which might be described as pharmacological parasympathetic denervation) differs from that of surgical denervation in that the weight of glands in cats does not decrease after atropine treatment [Emmelin, Jacobsohn and Muren, 1951]. In the present investigation the effects of atropine treatment were further studied, on the rat's submaxillary gland, and compared with those of parasympathetic denervation.…”
mentioning
confidence: 92%